Quantitative Measurement System of Liquid Products in Sealed Tank; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Shulgina Yu. V. Yulia Viktorovna; Kostina M. A. Maria Alekseevna; Sorokin P. V. Pavel Vladimirovich; Polonskaya M. S. Marina Sergeevna; Kozhemyak O. A. Olesya Anatolievna; Soldatov A. A. Andrey Alekseevich (2019, 2019)
Title screen